Comprehensive large-scale investigation and assessment of trace metal in the coastal sediments of Bohai Sea. Issue 1 (April 2018) - Li, Hongjun; Gao, Xuelu; Gu, Yanbin; Wang, Ruirui; Xie, Pengfei; Liang, Miao; Ming, Hongxia; Su, Jie
Abstract: The Bohai Sea is characterized as a semi-closed sea with limited water exchange ability, which has been regarded as one of the most contaminated regions in China and has attracted public attention over the past decades. In recent years, the rapid industrialization and urbanization around the coastal region has resulted in a severe pollution pressure in the Bohai Sea. Although efforts from official government and scientific experts have been made to protect and restore the marine ecosystem, satisfactory achievements were not gained. Moreover, partial coastal areas in the Bohai Sea seemingly remain heavily polluted. In this study, we focused on five coastal regions around the Bohai Sea to study the spatial distribution pattern of trace elements in the sediments and their ecological risk. A total of 108 sediment samples were analyzed to determine the contamination degree of trace elements (Cu, Cd, As, Pb, Zn, Cr, and Hg). Contamination factor ( CF ), pollution load index ( PLI ), geoaccumulation index ( I geo ), and potential ecological risk index ( PERI ) were utilized to assess the pollution extent of these metals. Spatial distribution patterns revealed that the sedimentary environments of coastal Bohai were in good condition, except Jinzhou Bay, according to the Marine Sediment Quality of China. The concentrations of Hg and Cd were considerably higher than the average upper crust value and presented high potential ecological risk and considerable potential ecological risk, respectively. The overall environment quality of the coastal Bohai Sea does not seem to pose an extremely serious threat in terms of metal pollution. Thus, the government should continue implementing pollution control programs in the Bohai Sea. Highlights: The coastal Bohai Sea sediments were in good condition except the Jinzhou Bay. Hg and Cd presented potential ecological risk in the studied area. The overall environment quality of the coastal Bohai Sea does not seem to be very serious in terms of metal pollution.